Alkali Iodide Deep Eutectic Solvents as Alternative Electrolytes for Dye Sensitized Solar Cells - Hugo Cruz; Ana Lucia Pinto; Noémi Jordão; Luísa A. Neves; Luís C. Branco (Sustainable Chemistry, 2021)
Different alkali deep eutectic solvents (DES), such as LiI:nEG, NaI:nEG, and KI:nEG, have been tested as electrolytes for dye sensitized solar cells (DSSCs). These DSSCs were prepared using pure DES or, alternatively, DES combined with different amounts of iodine (I2). The most important parameters, such as open circuit voltage (VOC), short circuit current density (JSC), fill factor (FF), and the overall conversion efficiency (η), were evaluated. Some DES seem to be promising candidates for DSSC applications, since they present higher VOC (up to 140 mV), similar FF values but less current density values, when compared with a reference electrolyte in the same experimental conditions. Additionally, electrochemical impedance spectroscopy (EIS) has been performed to elucidate the charge transfer and transport processes that occur in DSSCs. The values of different resistance (Ω·cm2) phenomena and recombination/relaxation time (s) for each process have been calculated. The best-performance was obtained for DES-based electrolyte, KI:EG (containing 0.5 mol% I2) showing an efficiency of 2.3%. The efficiency of this DES-based electrolyte is comparable to other literature systems, but the device stability is higher (only after seven months the performance of the device drop to 60%).